Transcranial Magnetic Stimulation for Long-Term Smoking Cessation: Preliminary Examination of Delay Discounting as a Therapeutic Target and the Effects of Intensity and Duration - Shevorykin, Alina; Carl, Ellen; Mahoney, Martin C.; Hanlon, Colleen A.; Liskiewicz, Amylynn; Rivard, Cheryl; Alberico, Ronald; Belal, Ahmed; Bensch, Lindsey; Vantucci, Darian; Thorner, Hannah; Marion, Matthew; et al. (Frontiers in Human Neuroscience, 2022)
Background: Repetitive transcranial magnetic stimulation (rTMS) is a novel treatment for smoking cessation and delay discounting rate is novel therapeutic target. Research to determine optimal therapeutic targets and dosing parameters for long-term smoking cessation is needed. Due to potential biases and confounds introduced by the COVID-19 pandemic, we report preliminary results from an ongoing study among participants who reached study end prior to the pandemic. Methods: In a 3x2 randomized factorial design, participants (n=23) received 900 pulses of 20Hz rTMS to the left dorsolateral prefrontal cortex in one of three Durations (8, 12, or 16 days of stimulation) and two Intensities (1 or 2 sessions per day). We examined direction and magnitude of the effect sizes on latency to relapse, 6-month point-prevalence abstinence rates, research burden, and delay discounting rates. Results: A large effect size was found for Duration and a medium for Intensity for latency to relapse. Increasing Duration increased the odds of abstinence 7-8 fold while increasing Intensity doubled the odds of abstinence. A large effect size was found for Duration, a small for Intensity for delay discounting rate. Increasing Duration and Intensity had a small effect on participant burden. Conclusions: Findings provide preliminary support for delay discounting as a therapeutic target and for increasing Duration and Intensity to achieve larger effect sizes for long-term smoking cessation and will provide a pre-pandemic comparison for data collected during the pandemic.